Prognostic implications of histological organ involvement in retroperitoneal sarcoma. Issue 5 (14th September 2021) - Tyler, R; Lee, M; Ierodiakonou, V; Hodson, J; Taniere, P; Almond, M; Ford, S; Desai, A
Abstract: Background: The prognostic significance of histological organ involvement by retroperitoneal sarcoma subtype is unknown. The present study aimed to describe organ involvement across the subtypes, and the implications for survival. Methods: Patients undergoing surgery for primary retroperitoneal sarcoma at the Queen Elizabeth Hospital, Birmingham from April 2005 to September 2018 were identified retrospectively. Histological organ involvement was classed as pushing, infiltrative or neither. Univariable and multivariable Cox regression models were produced to analyse the association between histological organ involvement and both overall (OS) and recurrence-free (RFS) survival for the cohort as a whole, and by histological subtype. Results: Data were available for a total of 197 patients, of whom 171 (86.8 per cent) had at least one organ resected. Infiltrative organ behaviour was seen in 37 patients (18.8 per cent), and pushing behaviour in 67 (34.0 per cent). For the cohort as a whole, infiltration (hazard ratio (HR) 4.32, 95 per cent c.i. 2.35 to 7.93; P < 0.001), but not pushing (HR 1.62, 0.90 to 2.92; P = 0.106), was associated with significantly shorter OS, in comparisons with a group with neither of these behaviours. However, this effect was found to differ significantly by histological subtype ( P = 0.009). For patients with dedifferentiated liposarcoma, there was no significant association between tumour behaviour and either OS ( P = 0.508) or RFS ( P = 0.313). However, in leiomyosarcoma, infiltrative behaviour was associated with shorter OS ( P = 0.002), and both infiltrative ( P < 0.001) and pushing ( P = 0.010) behaviours were associated with shorter RFS, compared with tumours with neither behaviour. Multivariable analyses of both OS and RFS returned similar results. Conclusion: The prognostic implications of organ involvement in retroperitoneal sarcoma vary by histological subtype. Abstract : The prognostic significance of histological organ involvement by retroperitoneal sarcoma subtype is unknown. The present study described organ involvement across the subtypes, and the implications for survival. The prognostic implications of organ involvement in retroperitoneal sarcoma were found to vary by histological subtype.